Novel partial overlapped gaussian pulse multi-access system aided by data analysis. (July 2022) - Alyassri, Salam; Ilyas, Muhammad; Marhoon, Ali; Bayat, Oguz
Abstract: Orthogonal frequency-division multi-access (OFDMA) systems have limited flexibility to improve efficiency due to their dependency on subcarrier orthogonality. As a result of this restriction, attention has shifted to a new multi-access communication method. The popularity of non-orthogonal multi-access (NOMA) systems is growing. Because the NOMA systems may broadcast and receive signals at various power levels, more complicated reception devices are required. Partially overlapped subcarriers or a non-orthogonal multi-access system are presented in this study. Instead of relying on the power level of sending signals, as is the case in present NOMA systems, the proposal relies on the benefit of modifying the shape of subcarriers to build a more efficient system. The authors propose Gaussian-pulse signals as an alternative to sites of concern for nature conservation (SINC) (SINC is the shape of subcarriers in OFDM). In this paper, there are several algorithms designed for this work. These algorithms control the distribution of frames on the transmitting subcarriers. They also calculate the width of the subcarriers as well as the spacing between the subcarriers to produce the lowest possible data error rate. The similarity values between the frames that will be sent will influence the values generated by these algorithms. So, these algorithms are to reduce the computational complexity of the system and obtain efficient channel capacity. The proposed model presents encouraging results for the bit error rate (BER) compared with OFDMA and ordinary NOMA systems. Also, Gaussian pulses with data analysis, as in the proposed schema, can achieve a reduction value in spectrum requirements by up to 13.8%. Besides, there is a decrease in out-of-band compared to OFDMA, which increases the spectrum efficiency. Finally, as compared to OFDMA, an improvement in BER with multipath fading and a Doppler frequency shifting environment was discovered in this research. Grahical abstract: Image, graphical abstract